2021
DOI: 10.14710/nmjn.v11i2.35257
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Ten-Week Short Message Service-Based Intervention on Self-Management of Type-2 Diabetes Patients in Bali, Indonesia

Abstract: Background: Diabetes mellitus is a chronic disease that may pose serious complications if poorly managed. The application of mobile technology (m-health) ranging from simple to more complex programs in diabetes management has the potential to foster patients’ active involvement in their care. However, the evidence of m-health effectiveness on the self-management of type-2 diabetes patients in low- and middle-income countries is still mixed.Purpose: To evaluate the effect of a ten-week short message system (SMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 27 publications
(36 reference statements)
0
14
0
Order By: Relevance
“…Among the 32 included studies [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ], 14 were from the United States, 3 from China, 2 from Spain, 2 from Australia, 2 from India, and 1 each from Australia, Iran, the United Kingdom, Slovenia, Sub-Saharan Africa, Canada, Belgium, Norway, Poland, and Italy. The studies ranged from 3 to 24 months of intervention between 2009 and 2021.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 32 included studies [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ], 14 were from the United States, 3 from China, 2 from Spain, 2 from Australia, 2 from India, and 1 each from Australia, Iran, the United Kingdom, Slovenia, Sub-Saharan Africa, Canada, Belgium, Norway, Poland, and Italy. The studies ranged from 3 to 24 months of intervention between 2009 and 2021.…”
Section: Resultsmentioning
confidence: 99%
“…Because there was no apparent allocation concealment, five [ 29 , 37 , 44 , 51 , 52 ] studies were rated as high risk. Twenty [ 23 , 24 , 25 , 27 , 28 , 29 , 31 , 33 , 34 , 35 , 36 , 37 , 44 , 45 , 46 , 47 , 50 , 51 , 52 , 53 ] studies were also rated as unclear bias because they were not blinded to interventionists or subjects. One [ 42 ] study was rated as high risk because it was not blinded to the outcome evaluator.…”
Section: Resultsmentioning
confidence: 99%
“…Slightly less than half originated in the United States (14/30, 47%). Studies are listed in chronological order and alphabetically: 2020 (n=19), 29–47 2021 (n=8), 48–55 2022 (n=3). 56–58 For each study, we extracted the following data fields: participants, intervention, comparison (to control or other group), medical outcomes, study design, sample size, bias within study, country of origin, statistics used, patient satisfaction, quality associated with intervention, barriers to adoption, strength of evidence, and quality of evidence.…”
Section: Resultsmentioning
confidence: 99%
“… Significant improvement in diet, exercise, smoking cessation, and BGL control. RCT Damayanti et al 47 Older adults, average age 61, 50% male, SMS Improved diet, exercise, blood-glucose testing, and foot care Improved blood-glucose testing, and foot care Quasi-experimental Fu et al 48 Older adults mHealth apps and SMS Improved self-management behaviors Improved self-management behaviors Qualitative Jia et al 49 Older adults mHealth enabled hierarchical diabetes management Overall improvement of HbA1C, but no statistically significant differences in weight changes. Improved HbA1C RCT Lee et al 50 Older adults mHealth apps and coaching Improved self-management behaviors Improved HbA1C RCT Lewinski et al 51 Older adults mHealth No control group Not reported Qualitative Li et al 52 Older adults mHealth app and wearable sensor Intervention group showed larger increase in cardiopulmonary endurance, larger decrease in body fat percentage Increase in cardiopulmonary endurance, decrease in body fat percentage RCT Montero et al 53 Older adults, average age 56.1, 81% Black, 62% female Cellular remote monitoring, Biotel system dashboard + telemedicine visits Statistically significant difference in HbA1C levels between groups as well as user confidence in self-management Improvement in HbA1C True ex...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation